Effects of Dark Triad on Transformational,_x000D_ Transactional and Laissez-Faire Leadership Styles - EKİZLER, HÜSEYİN (My University, 2020)
Aim of this research is to examine effects of dark triad personality traits (Machiavellianism, narcissism,and psychopathy) on Transformational, Transactional and Laissez Faire leadership styles. Data for theresearch are collected through questionnaire surveys using convenience sampling method. To measureDark Triad traits Dirty Dozen scale developed by Jonason and Webster (2010), to measure leadershipstyles Multifactor Leadership Questionnaire (MLQ 5x) developed by Bass and Avolio (1995) are used.Exploratory Factor Analyses are conducted to dirty dozen and MLQ 5x scales. Dark triad traits areextracted into three, transformational leadership is extracted into two, transactional leadership is extracted into three and laissez faire leadership is extracted into a single factor. Correlation, General LinearModel and multiple regression analyses are conducted using all factors obtained. Results showed significant effect of Dark Triad traits on leadership styles. Also, regression analyses indicated positive effectof dark triad constructs on laissez faire, negative effect of Machiavellianism and psychopathy on transformational and contingency reward, positive effect of narcissism and psychopathy on management byexception passive, positive effect of Narcissism on management by exception active leadership styles.The implications of the results are discussed and future research areas are suggested.

Bu çalışmanın amacı karanlık üçlüyü oluşturan kişilik özellikleri olan Makyavelizm, narsisizm ve_x000D_ psikopatinin dönüşümsel, etkileşimsel ve serbest bırakıcı liderlik tarzları üzerindeki etkilerinin incelenmesidir. Araştırma verileri kolayda örnekleme yöntemi kullanılarak internet üzerinden anket uygulanması ile elde edilmiştir. Karanlık üçlüyü ölçmek için Jonason ve Webster tarafından 2010 yılında_x000D_ geliştirilen Karanlık Üçlü ölçeği (Dirty Dozen), liderlik tarzlarını ölçmek için ise Çok Faktörlü Liderlik_x000D_ Ölçeği (MLQ 5x) kullanılmıştır. Araştırma verilerine öncelikle keşfedici faktör analizi yapılmıştır._x000D_ Karanlık üçlü üç, dönüşümsel liderlik iki, etkileşimsel liderlik üç faktöre ayrılmış, serbest bırakıcı liderlik_x000D_ ise tek faktör olarak belirlenmiştir. Geçerliliği ve güvenirliliği tespit edilen faktörler kullanılarak korelasyon, genel lineer model ve çoklu doğrusal regresyon analizleri yapılmıştır. Sonuçlar karanlık üçlü özelliklerinin liderlik tarzlarını anlamlı biçimde etkilediğine işaret etmektedir. Regresyon analizleri karanlık_x000D_ üçlünün tüm alt boyutlarının serbest bırakıcı liderlik üzerinde pozitif etkisinin bulunduğunu, Makyavelizm ve psikopatinin dönüşümsel ve koşullu ödüllendirme üzerinde negatif etkisinin bulunduğunu,_x000D_ narsisizm ve psikopatinin istisnalarla yönetim – pasif üzerinde pozitif etkisinin bulunduğunu ve narsisizmin istisnalarla yönetim- aktif üzerinde pozitif etkisinin bulunduğunu göstermektedir. Araştırma_x000D_ bulguları sonuç bölümünde tartışılmıştır.
Karanlık Üçlünün Dönüşümsel, Etkileşimsel ve Serbest Bırakıcı Liderlik Tarzları Üzerindeki Etkilerinin İncelenmesi